Teaching Language and Language Culture in Grammar School Curricula for the Subject Serbian Language and Literature - Mihajlović, Jelena D. (Collection of Papers of the Faculty of Philosophy in Priština, 2023)
The paper gives a review of high school curricula for Serbian language and literature—the topics of Language and Language Culture from 1990 to the present. The structure, tasks, and contents of the curricula from 1990 and 1991, the innovated curriculum from 2011, and the latest, reformed curriculum were reviewed, analysed, and compared. The comparison aims to determine and analyse their similarities and differences in the field of language and language culture, to observe and highlight their positive and negative aspects, and thus, in accordance with the research results, to draw conclusions and finally make suggestions that would contribute to their further improvement.
Keywords: grammar school; curriculum; syllabus; language teaching; language culture teaching